HGG-03. EVEROLIMUS TREATMENT IMPROVES THE CNS PENETRATION AND EFFICACY OF DASATINIB IN THE TREATMENT OF PDGFRA-DRIVEN PEDIATRIC HIGH-GRADE GLIOMA AND DIFFUSE INTRINSIC PONTINE GLIOMA. (23rd April 2019) - Miklja, Zachary; Mullan, Brendan; Stallard, Stefanie; Yadav, Viveka Nand; Bruzek, Amy K; Garcia, Taylor; Leonard, Marcia; Robertson, Patricia L; Paul, Alyssa; Pai, Manjunath P; Phoenix, Timothy; Marini, Bernard; et al.
Abstract: Pediatric high-grade glioma (HGG) and diffuse intrinsic pontine glioma (DIPG) frequently harbor alterations in PDGFRA . The CNS penetration of PDGFRA inhibitors, such as dasatinib, is limited by the tumor-efflux protein P-glycoprotein (P-gp). We hypothesized that co-treatment with everolimus, which has been shown to block P-gp in non-tumor models, would increase CNS penetration and efficacy of dasatinib in PDGFRA-driven HGG and DIPG. Dasatinib effectively treated mouse DIPG cells generated from an intra-uterine electroporation (IUE) model ( TP53, PDGFRA and H3K27M mutations), with an IC50 of 100 nM and a dose-dependent reduction in PDGFRA and pPDGFRA by western blot. Using an in vitro P-gp inhibitor assay, we confirmed that everolimus strongly blocks P-gp activity at 1 uM (p=0.0028 vs untreated, and NS vs complete P-gp block). Treatment studies using the IUE model are ongoing. Brief treatment with everolimus resulted in sub-IC50 dasatinib average mouse cortex (23 nM) and tumor (65 nM) concentrations by mass spectroscopy, but prolonged (>24 hours) everolimus exposure resulted in improved average cortex (288 nM) and brainstem tumor (360 nM) concentrations. Based on this promising pre-clinical data, we established a phase 2 trial employing dasatinib and everolimus in children with HGG and DIPG that contain PDGFRA alterations (NCT03352427). The first two patients (a recurrent PDGFRA -amplified HGG and a recurrent PDGFRA D842V-mutated DIPG) treated with dasatinib and everolimus after re-irradiation survived 6 months and 9 months (ongoing), respectively, after progression, which compares very favorably to historical controls. Paired CSF samples (before and after addition of everolimus) from the PDGFRA -amplified patient showed a 50% increase in CSF dasatinib level after addition of everolimus. In summary, we demonstrate that dasatinib treatment of PDGFRA-driven pediatric HGG and DIPG is improved with everolimus blockade of P-gp. This represents a novel route for improving the CNS penetration and efficacy of precision therapies for pediatric HGG.